2011
DOI: 10.1504/ijpqm.2011.043011
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of Six Sigma implementation in medium scale Indian automotive enterprises

Abstract: This research paper explores the status and imminent factors for evaluating the feasibility of implementing Six Sigma in medium scale Indian automotive industry. The research methodology, designed using quantitative approach, reports 30 medium scale automobile enterprises started implementing Six Sigma during survey range of 2009-2010 from west India. The research finding shows diversified practices of traditional quality initiatives, e.g. ISO 9000, total quality management, Kaizen, etc. over Six Sigma as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Six Sigma has been carried out in multiple sectors. We find case studies conducted in automotive industry (Sambhe and Dalu, 2011;Surange, 2015;Valles et al, 2009), electronics (Choi et al, 2012;Patterson et al, 2005), construction (Negi et al, 2017;Siddiqui et al, 2016;Stewart and Spencer, 2006), health care (Antony et al, 2018;Benedetto, 2003), banking (Sunder, 2016;Sunder and Antony, 2015), tourism (Pearlman and Chacko, 2012), airlines (Gibbons et al, 2012), among others. Thus, it was observed that Six Sigma has been widely implemented with different objectives in industrial and services companies (Raja Sreedharan and Raju, 2016;Sunder et al, 2018).…”
Section: Food Can Manufacturing Industry and Six Sigmamentioning
confidence: 83%
“…Six Sigma has been carried out in multiple sectors. We find case studies conducted in automotive industry (Sambhe and Dalu, 2011;Surange, 2015;Valles et al, 2009), electronics (Choi et al, 2012;Patterson et al, 2005), construction (Negi et al, 2017;Siddiqui et al, 2016;Stewart and Spencer, 2006), health care (Antony et al, 2018;Benedetto, 2003), banking (Sunder, 2016;Sunder and Antony, 2015), tourism (Pearlman and Chacko, 2012), airlines (Gibbons et al, 2012), among others. Thus, it was observed that Six Sigma has been widely implemented with different objectives in industrial and services companies (Raja Sreedharan and Raju, 2016;Sunder et al, 2018).…”
Section: Food Can Manufacturing Industry and Six Sigmamentioning
confidence: 83%
“…The success of Six Sigma has been restricted to large organizations while small- and medium-sized enterprises (SMEs) have been lagging far behind due to the lack of awareness of its importance, methods and desired outcomes among the SMEs. A recent study shows that, even in developed countries, only 67.5 percent of employees in SMEs were aware of the Six Sigma methodology (Sambhe and Dalu, 2011). Psychogios and Tsironis (2012) claimed that even at the top management level, such awareness of various quality excellence practices is limited.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sambhe [33] identified fifteen critical success factors for Six Sigma implementation, and ranked them based on the survey results he obtained from medium-scale automotive industries in India. These are (in descending order): Based on the combined success factors identified in this previous research, semi-structured interviews were undertaken with 14 Six Sigma Master Black Belts and Black Belts from Lonmin who were involved in the original deployment programme.…”
Section: Literature Survey On Success Factors For Six Sigma Deploymentmentioning
confidence: 99%